Aktifitas Ekstrak Metanol Kulit Buah Manggis (Garcinia mangostana L) terhadap Crocidolomia pavonana Fabricius (Lepidoptera: Crambidae): English - Arneti, Arneti; Liswarni, Yenny; Sinaga, Ismi Fadhilah (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2018)
Crocidolomia pavonana is an important pest of Brassicaceous which can be controlled by botanical insecticide. The objective of this study was to determine activity of the mangosteen peel fruit (G. mangostana) methanol extract on mortality and development of C. pavonana. The research was conducted at laboratory. The design used was a completely randomized design with four level of methanol extract of the mangosteen peel fruit on larva of 2nd instar. The extract was tested to larvae by a leaf-residue feeding method without selection. The parameters were mortality, antifeedant activity, developmental time, and numbers of pupae C. pavonana formed. The results showed that methanol extract of the mangosteen peel fruit was less effective in controlling C.pavonana. The highest concentration of extract (0.5%) caused mortality 72%, antifeedant activity 55,70%, extended larval developmental time and inhibited numbers of pupae formed of 30,66%.